A Research on the Automation and Network of Libraries: Exploring the Affordability, Application, and Challenges of Library Automation Tools (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the fields of library, computer science and library automation in particular, the growth and advancement of information and communications technology (ICT) plays an important role. This analysis also offers a statistical view of the programme packages that libraries and the modules use for the automation of libraries. This report shows studies on the automation and networking of libraries. The research focuses primarily on affordability, application and challenges confronting Library Automation Tools throughout the installation and usage phase.